Estudio antropológico de las alquerías de Benizahat y Zeneta (Vall d´Uixó, Castellón). Una ventana a la vida rural andalusí - Olivé-Busom, Júlia; López-Costas, Olalla; Márquez-Grant, Nicholas; Kirchner, Helena (Universitat de Valencia, 2021)
During the Andalusi period, modern day Vall d'Uixó (Castellón, Spain) was formed by a series of hamlets that were inhabited by Islamic population until the 16th century. Through the anthropological analysis of 99 skeletons from two of these hamlets, Benizahat and Zeneta, this study explores the possible existence of differences in the lifestyle of males and females and occupational stress related to the rural economy of this population. In addition, their living conditions and stress levels during growth are assessed through the confrontation with other peninsular Islamic populations. Although the studied sample is not clearly distinguishable from other Andalusian populations in terms of physiological and occupational stress, the significant differences in the distribution of Schmörl’s nodes between males and females and the high frequencies of dental caries in the population should be highlighted.
Anthropological study of Benizahat and Zeneta hamlets. A window into Andalusian rural life
Keywords: šarq al-Andalus; physiological stress; health status; Islamic archaeology; cemetery